Proactive integrated mental health care (PIMHC) model for hospitalized surgical patients: Development and feasibility study - Kewithinwangbo Newme; Abhilash Goyal; Jay Kishor Soren; Ashok Puranik; Nibedita Das; Ramdas Ransing (Journal of Neurosciences in Rural Practice, 2026)
Objectives: Mental health disorders (MHDs) adversely affect the surgical outcomes, including pain, hospital stay, complications, and mortality. Proactive consultation–liaison (C-L) psychiatry models are widely used for surgical patients in high-income countries, but they have yet to be developed and systematically evaluated in Indian healthcare settings. The present study aims to develop and evaluate the feasibility of a proactive integrated mental health care (PIMHC) model for surgical inpatients in a tertiary center in Northeast India. Materials and Methods: This study was conducted between August 2024 and August 2025 in two sequential phases of 6 months each: (1) development of the PIMHC model, and (2) study to assess its feasibility. In the first phase, a desk literature review focused on various aspects of the C-L psychiatry model was conducted to develop a preliminary PIMHC model. A panel of experts and stakeholders reviewed the proposed models, suggested modifications, and co-developed the final components suitable for the Indian context. The finalized PIMHC model was subsequently tested using a single-arm study design in a tertiary care teaching hospital to assess feasibility, based on predefined indicators such as screening rates and dropout rates. Results: The co-developed PIMHC model included nurse-led screening of admitted surgical patients using validated tools, followed by proactive psychiatric consultation and planned follow-ups at 2, 4, and 6 weeks. Of 61 patients screened for eligibility, 57 were enrolled. 36 participants (63.2%) completed screening, while 21 had incomplete forms due to the length of the tools, language barriers, and staff workload. Among those who completed screening, 10 participants (27.8%) screened positive and all received psychiatric consultation. At 2 weeks, follow-up was completed by 40% of screen-positive and 23% of screen-negative participants. Conclusion: The model demonstrates preliminary operational feasibility within a tertiary-care surgical setting, but requires refinement, simplification of screening processes, and structured follow-up mechanisms before further implementation and evaluation for its effectiveness.